KALDELLIS, Anthony. Romanland: Ethnicity and Empire in Byzantium. Cambridge, MA: Harvard University Press, 2019. 392p. - Welte Bernardo, Guilherme (Revista Diálogos Mediterrânicos, 2020)
KALDELLIS, Anthony. Romanland: Ethnicity and Empire in Byzantium. Cambridge, MA: Harvard University Press, 2019. 392p.